Modal analysis for small engine crankshaft - Santhana Julias, Henry (2010)
This thesis consists of finding the mode shape and natural frequency of a 4 stroke motorcycle engine crankshaft. The test is done in both simulation and also experimental using a simple test rig. The crankshaft is modeled using Solidworks computer aided design (CAD) software and simulation analysis is done in ALGOR computational aided engineering (CAE) software. Experimental is done by using impact hammer to excite the crankshaft and data recorded using data acquisition system (DAS) connected to sensor located on the crankshaft. The results for both simulation and experimental is compared. The final selected natural frequency for simulation is based on mesh aspect ratio of 60%. Simulation natural frequency in 1st mode is 1044.9 Hz (bending in face off), 2nd mode is 1204.59 Hz (bending in face axis), 3rd mode is 2104.59 Hz (bending out of face), 4th mode is 2174.66 Hz (bending out of face) and 5th mode is 2624.24 Hz (bending out of face). Meanwhile, the experimental natural frequency in 1st mode is 990.01 Hz, 2nd mode is 1244 Hz, 3rd mode is 2084.89 Hz, 4th mode is 2219.11 Hz and 5th mode is 2791.18 Hz. The discrepancy errors recorded between simulation and experimental is ranging from 0.94 – 6.56 %.